2023
DOI: 10.3389/fpsyg.2023.1067872
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between alexithymia and food addiction: The Finnish version of Yale Food Addiction Scale and preliminary test of its psychometric properties

Abstract: BackgroundIt has long been suggested that addictive behaviors are associated with alexithymia, a personality trait characterized by difficulties in emotional awareness and expression. However, little is known about the role of alexithymia in food addiction.ObjectivesThe aim of this study was to investigate the relationship between alexithymia and food addiction. As part of the study, the validity of the Finnish version of Yale Food Addiction Scale (YFAS-F) was also investigated.MethodsThe sample consisted of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…Moreover, we found that females showed more relevant alexithymic traits than males (as detected by the TAS-20), especially in the domain of an inadequate identification of feelings. This finding is partially in line with the literature and could be explained with the more frequent occurrence of eating spectrum traits in females than in males: the 'psychopathological core' of alexithymia is characterized by a marked difficulty in emotions' identification and elaboration and by a significant interference with self-regulation processes predisposing to dysfunctional eating behaviors, such as binge-eating [38][39][40] or emotional eating [41]. However, several studies pointed out that alexithymic traits might be more frequent among males than females as a consequence of the so-called 'normative male alexithymia' [42], characterized by a deficit in processing emotions.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, we found that females showed more relevant alexithymic traits than males (as detected by the TAS-20), especially in the domain of an inadequate identification of feelings. This finding is partially in line with the literature and could be explained with the more frequent occurrence of eating spectrum traits in females than in males: the 'psychopathological core' of alexithymia is characterized by a marked difficulty in emotions' identification and elaboration and by a significant interference with self-regulation processes predisposing to dysfunctional eating behaviors, such as binge-eating [38][39][40] or emotional eating [41]. However, several studies pointed out that alexithymic traits might be more frequent among males than females as a consequence of the so-called 'normative male alexithymia' [42], characterized by a deficit in processing emotions.…”
Section: Discussionsupporting
confidence: 88%
“…This suggests a parallel between FA and substance use disorders. Precisely, as indicated, FA and drug use disorders share analogous etiological variables such as impulsivity ( 85 ) and anxiety ( 30 , 86 ). This result demonstrates that high drive levels are related to higher values in FA ( 87 ).…”
Section: Discussionmentioning
confidence: 95%
“…Alexithymia, a concept first defined by Sifneos (1977), is defined as the individual's difficulty in recognizing and defining emotions both in themselves and in others, and in distinguishing between bodily sensations, emotions, and cognitions (Parker, Keefer, Taylor, & Bagby, 2008). Alexithymia is a multidimensional personality structure that includes difficulty in identifying one's emotions and distinguishing them from bodily sensations; difficulty in expressing one's emotions to others; and a utilitarian and extroverted cognitive style that does not involve emotional reactions when faced with stressful situations (Li et al, 2023;Taylor et al, 1997;2016). The concept of alexithymia, which can be found in Turkish sources with expressions such as thought slavery (Dökmen, 2000) and emotional crassness (Şahin, 1996), can also be defined as the lack of emotional awareness.…”
Section: Introductionmentioning
confidence: 99%